Physio-Treadmill (PhyMill): Ergonomics Evaluation of Posture Impact on Kids with Cerebral Palsy using Digital Human Modeling (DHM) Simulation - Rabiatul Aisyah, Ariffin; Mohd Azrul Hisham, Mohd Adib; Nurul Shahida, M. S.; Narimah, Daud; Nur Hazreen, Mohd Hasni (IEEE, 2021)
Musculoskeletal disorders (MSDs) are very common in people who pursue physiotherapy. Ideally, ergonomics should be taken into consideration in all areas of life, including in the clinic, workplace, and home. Therefore, this study aims to evaluate the optimum posture impact of the kid with cerebral palsy (CP) using the PhyMill product through the DELMIA V5 R20 Rapid Upper Limb Assessment (RULA) analysis. The collection of data started with observation and interviews with the children. Then, the development of the virtual environment for ergonomics analysis is used. The research was conducted in three conditions; sitting on a harness, standing on PhyMill, and walking on PhyMill. As a result, sitting on the harness posture was very dangerous and must be adjusted immediately. The task should be amended in order to resolve the health complications for the children.